2011
DOI: 10.1016/j.ajpath.2010.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Natural Regulatory T Cells Control Coronary Arteriolar Endothelial Dysfunction in Hypertensive Mice

Abstract: Coronary artery disease in patients with hypertension is increasing worldwide and leads to severe cardiovascular complications. The cellular and molecular mechanisms that underlie this pathologic condition are not well understood. Experimental and clinical research indicates that immune cells and inflammation play a central role in the pathogenesis of cardiovascular diseases. Recently, it has been reported that CD4(+)CD25(+) regulatory T cells (Tregs) regulate heart fibrosis in hypertension. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(104 citation statements)
references
References 38 publications
4
96
2
Order By: Relevance
“…Several groups have shown that adoptive transfer of Tregs lowers BP and ameliorates cardiac and renal injury in different models of hypertension. [65][66][67][68] Mice deficient in IL-10, an important product of Tregs, develop similar degrees of hypertension in response to angiotensin II, but have severe endothelial dysfunction and vessels from these mice show an increased superoxide production when incubated with angiotensin II. 69 These and other data suggest that Treg-derived IL-10 mediates the beneficial effects of Tregs in hypertension.…”
Section: Tregs and Il-10mentioning
confidence: 99%
“…Several groups have shown that adoptive transfer of Tregs lowers BP and ameliorates cardiac and renal injury in different models of hypertension. [65][66][67][68] Mice deficient in IL-10, an important product of Tregs, develop similar degrees of hypertension in response to angiotensin II, but have severe endothelial dysfunction and vessels from these mice show an increased superoxide production when incubated with angiotensin II. 69 These and other data suggest that Treg-derived IL-10 mediates the beneficial effects of Tregs in hypertension.…”
Section: Tregs and Il-10mentioning
confidence: 99%
“…The CD4 TREGs 46,52 and B cells 63 have been observed to mediate vascular physiology and pathology. To begin to determine the potential role played by the interaction between CD8 T cells and B cells in the absence of CD4 T cells in PP vascular physiology, and to address the relatively low systemic levels of CD8 T cells in the adoptive transfer experiments, we began the analysis of vessels from PP CD4-deficient mice 57 ( Figure 8).…”
Section: Prepregnancy Establishment Of Cd8 T Cells In Rag1mentioning
confidence: 99%
“…[46][47][48][49] Because of these characteristics, we examined the effects of CD8 T-cell reconstitution in Rag1 ÀÀ mice. In light of the potential role played by CD4 TREGs in the immune homeostasis of pregnancy 18,50 and in the modification of cardiovascular disease, 46,[51][52][53][54] we also examined mice with genetic deficiency in CD4 T cells. 55 We chose mesenteric vessels because of their role in the regulation of systemic blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, hypertension inhibited IL-10 and HO-1 expression, with a resultant increase in ALT to a level higher than that caused by the CDAA diet alone. In addition, indirect evidence indicates that IL-10 exerts a protective effect on endothelial function in diabetes and hypertension (17,30). IL-10 has also been shown to inhibit the activation of hepatic stellate cells and decrease hepatic fibrosis and apoptosis in a CCl4-induced rat liver fibrosis model (31,28).…”
Section: Cdaa Diet --------------------------------------------------mentioning
confidence: 99%